Analysis of Time and Cost Planning and Control for Waterproofing Work in Project X Multi-Story Data Center Jakarta - Ardiansyah, Giri Teguh; Bayuaji, Ridho; Asmi, Ade; Darmawan, Muhammad Sigit; Suswanto, Budi Suswanto (Newinera Publisher, 2025)
Waterproofing plays a crucial role in maintaining a building's integrity. However, subcontractor skill limitations and project constraints such as design changes, site readiness, and resource shortages often cause delays. This study analyses the planning and time control of waterproofing work in the Building X High-Rise Data Center project, covering eight work items. Using the Precedence Diagram Method (PDM), the work schedule indicates an effective duration of 34 weeks. The analysis methods used include Critical Path Method (CPM), Earned Value Analysis (EVA), Program Evaluation Review Technique (PERT), and crashing for project duration optimization. By the 30th week, the calculation results showed a Schedule Performance Index (SPI) of 0.96 and a Schedule Variance (SV) of -Rp120,057,209.0, indicating project schedule delays. In terms of cost, the Cost Performance Index (CPI) was 0.99, and the Cost Variance (CV) was -Rp26,459,888.0, showing cost overruns, though still within a relatively controlled limit. The probability of project completion reached 90% by the 30th week. Optimization through acceleration methods proved effective in reducing project duration with controlled additional costs. Therefore, better mitigation strategies are needed to minimize time and cost deviations in similar future projects.